Some aspects of morphophysiography of Labeo calbasu (Ham.) from Rana Pratap Sagar reservoir, Rajasthan - Choudhary, C S; Sharma, L L; Sharma, S K; Saini, V P (Indian Journal of Fisheries, 2011)
Length-weight relationship for any fish species gives its performance and well being in relation to habitat and helps in monitoring the status offish stock for obtaining optimum yield. These relationships may vary from time to time in the same water body due to alterations in water quality and fish stocks. Studies on length-weight relationships and condition factors have widely attracted the attention of fishery biologists O^ao and Rao 1972, Kumar 1988). However, on Rajasthan waters such researches are comparatively meagre